Standard for Rehabilitation Diagnosis and Treatment of COVID-19 with Integration of Traditional Chinese and Western Medicine - Wenguang XIA; Qiang HUA; Gang WANG; Tiecheng GUO; Shanshan ZHU; Yan ZHAO; Jun TIAN; Chanjuan ZHENG; Yangpu ZHANG; Wei ZHANG; Qiang TANG; Rongjiang JIN; et al. (康复学报)
Fighting against the epidemic of Corona Virus Disease 2019 (COVID-19) has been successfully in this stage in China. The National Health Commission has proposed that rehabilitation medical institutions should provide assessment of pulmonary function and provide the management of respiratory rehabilitation for patients discharged with severe and critical COVID-19 infection. In response to this proposal, Hubei Provincial Hospital of Integrated Chinese and Western Medicine had established a COVID-19 Rehabilitation Department during the early stages of the pandemic and had been delivering clinical care according to National Rehabilitation Guidelines. According to clinical classification of the disease, the syndrome differentiation and treatment of traditional Chinese Medicine, we adopted personalized rehabilitation programme with integrated Chinese and western medicine, which include modern rehabilitation therapeutic techniques, such as positional therapy, breathing training and kinesiotherapy with the purpose of ameliorating respiratory and physical function, point massage, sandwiched moxibustion and other Chinese medicine treatments to regulate Qi (breathing) activities and repair Zang-fu viscera function, traditional Chinese exercises such as Tai Chi boxing and Baduanjin exercise with the effects of strenthening physical ability and improving physical and mental status. These Patients do benefit from this combined rehabilitation through clinical observation. Based on our clinical experience, we have formulated a standard protocol for patients with COVID-19 as a reference for rehabilitation professionals in application of traditional Chinese and western rehabilitation, with the aim of promoting universal function and quality of life for the patients.